Pengaruh Produk, Harga, Promosi, dan Distribusi terhadap Keputusan Pembelian Konsumen UMKM Kuliner di Jakarta Timur - Rismawati, Henny; Mulyadi, Mulyadi (Universitas Negeri Makassar, 2025)
This study aims to analyze the influence of product, price, promotion, and distribution on consumer purchasing decisions in culinary Micro, Small, and Medium Enterprises (UMKM) in East Jakarta. Culinary MSMEs play a vital role in the local economy but face marketing challenges in attracting and retaining consumers amid intense competition. A quantitative approach was employed through a survey of 100 consumers selected using purposive sampling. The research instrument was a Likert-scale questionnaire (1–5), and the data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, as well as t-test and F-test.The findings indicate that product, price, promotion, and distribution each have a positive and significant effect on purchasing decisions. Among these, product emerged as the most influential factor. Simultaneously, all four variables significantly affect consumer purchasing decisions, with an Adjusted R² value of 0.580, suggesting that 58% of the variation in purchasing decisions can be explained by these marketing mix elements. The study highlights the importance of integrating product, price, promotion, and distribution strategies to strengthen the competitiveness of culinary UMKM, particularly in urban areas with dynamic consumer behavior such as East Jakarta